PREFERENSI MINAT MASYARAKAT MELAKUKAN TRANSAKSI TERHADAP LEMBAGAKEUANGAN SYARIAH DAN LEMBAGA KEUANGAN KONVENSIONAL DI DUSUN BANYUMAS DESA KLAMPAR KECAMATAN PROPPO KABUPATEN PAMEKASAN - Matnin Matnin; Abdul Bari (Assyarikah: Journal of Islamic Economic Business, 2020)
According to the Law of the Republic of Indonesia Number 10 of 1998 concerning Banks, "the law states that, a body that manages funds from the public in the form of savings and then distributes them back to the community in and performs other services in the context of welfare. Public. Meanwhile, the definition of a sharia bank according to the Law of the Republic of Indonesia Number 21 of 2008 concerning Islamic Banking contained in article 1 paragraph 7, "that a sharia bank is a business that is run according to the principles of Islamic law and then distributes it in the form of financing based on the principle of buying and selling, for results, and services. ".The public interest preference in question is a tendency, preference or desire in choosing to transact at a financial institution, both Islamic financial institutions and conventional financial institutions. Indicators of the tendency to choose transactions in financial institutions, both Islamic financial institutions and conventional financial institutions, include environmental influences, religious (avoiding usury), advertising and promotion, products, services, needs and access to service offices,The problem in this research is, how is the preference of the Banyumas Hamlet people in conducting transactions towards Islamic financial institutions and conventional financial institutions?To answer these problems, researchers will use primary and secondary data ranging from direct observation, interviews, and documentation to literature studie